2013
DOI: 10.1155/2013/425369
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Pharmacological Review of Da Chuanxiong Formula: A Famous Herb Pair Composed ofChuanxiong RhizomaandGastrodiae Rhizomafor Headache

Abstract: Chronic headache such as migraine and nervous headache has become one of the most common locations of pain and one of the most difficult diseases to recover due to its numerous causes and inconvenience to keep acesodyne administration for a long time. However, there are a series of treatment theories and herbal formulas for this disease in traditional Chinese medicine (TCM), in which Da Chuanxiong formula (DCXF), a herb pair composed of Chuanxiong Rhizoma (CR), Chuanxiong in Chinese, and Gastrodiae Rhizoma (GR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Studies have shown that DCXF possesses therapeutic effects on stroke, dementia, vertigo, and headache, and is mediated by improvement of blood vessel elasticity and cerebral blood supply, reduction of blood–brain barrier (BBB) disruption, intracellular free calcium concentration, and edema formation. It also inhibits inflammation and nerve cell apoptosis . In lipopolysaccharide (LPS)‐incited RAW 264.7 cells, DCXF inhibited the productions of NO and PGE2 by suppressing COX‐2 and iNOS expressions …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that DCXF possesses therapeutic effects on stroke, dementia, vertigo, and headache, and is mediated by improvement of blood vessel elasticity and cerebral blood supply, reduction of blood–brain barrier (BBB) disruption, intracellular free calcium concentration, and edema formation. It also inhibits inflammation and nerve cell apoptosis . In lipopolysaccharide (LPS)‐incited RAW 264.7 cells, DCXF inhibited the productions of NO and PGE2 by suppressing COX‐2 and iNOS expressions …”
Section: Resultsmentioning
confidence: 99%
“…It also inhibits inflammation and nerve cell apoptosis. 112 In lipopolysaccharide (LPS)-incited RAW 264.7 cells, DCXF inhibited the productions of NO and PGE2 by suppressing COX-2 and iNOS expressions. 111 Treatment with DCXF aqueous extract 1 week before and 11 days after the induction TBI by a CCI model in rat improved the learning ability, memory retention, and proliferation of neural stem cells (NSCs).…”
Section: Crocus Sativusmentioning
confidence: 99%
“…We have previously observed that the elevated [Ca 2+ ] i in hypoxic PASMCs is largely mediated by enhanced SOCE through SOCC (Shimoda, Wang, & Sylvester, 2006). The hypoxia‐enhanced SOCE is mediated by the hypoxic up‐regulation of canonical TRPC1 and TRPC6 ion channels, the main components of SOCC in PASMCs (Hou et al, 2013; Li et al, 2013; Malczyk et al, 2013; Wang et al, 2013; Wang et al, 2013; Wang et al, 2014; Xia et al, 2014; Zhang et al, 2013). The data from this study further indicate that the therapeutic effect of TMP is due, at least partly, to its down‐regulation of TRPC channel expression and inhibition of intracellular Ca 2+ signalling in PASMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Chuanxiong could promote blood and Qi circulation and dispel wind and relieve pain according to TCM theory, and has been used for headache for thousands of years in traditional Chinese, Japanese, and Korean folk medicine. 63 In the past decades, the main chemical compositions such as ligustrazine, the volatile oil and Ferulic acid and their pharmacological mechanisms of Chuanxiong have been well studied as follows: (A), Ligustrazine could prevent blood vessel spasm probably through inhibiting Ca 2+ inner flow in blood vessel smooth muscle cell, improving calcium pump activity, increasing calcium outer flow, and blocking adrenal gland recipient-␤ of blood vessel smooth muscle. 64 (B), Volatile oil is related to its effects of Table 4 Adverse events of the included studies.…”
Section: Implication For Practicementioning
confidence: 99%